PENANGGULANGAN DEKADENSI MORAL REMAJA MELALUI PENDIDIKAN KARAKTER DAN PEMBINAAN ADABDI MULYASARI MANDE - Hidayat, Didin (LPPM STAI Al-Azhary Cianjur, 2022)
Moral decadence is the deterioration of good behavior, actions, character or morals to be bad, in other words the occurrence of disobedience of the rules, inappropriateness in socializing dan impoliteness in interacting with others. Moral decadence continues to afflict the lives of today's teenagers, which increasingly undermines their circumstances and relationships, so that it has a very bad impact on the lives of adolescent in the future. Therefore, actually the main role in this case is the family, because the family is harmonious, respectful, open, positive communication, and there is love affection, then the process of socializing values where norms will be conveyed to adolescent is well delivered. In addition efforts to foster of moral values in adolescents are also carried out in every educational institution. Conducive educational institution and mutual respect, then the transinformation can be well received.